Problem-Solving and Educational Management Strategies Among Preschool Principals in Early Childhood Settings - Kamtini, Kamtini; Simaremare, Aman; Tanjung, Salsabila Hasiana; Hasim, Zuwati (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2025)
The ability of preschool principals to solve problems effectively is crucial in ensuring the smooth operation of early childhood education institutions. Preschool principals are key in managing administrative tasks, teacher performance, curriculum implementation, and parent-school relationships. However, challenges such as limited resources, staff conflicts, and adapting to educational policies require strong problem-solving skills. This study aims to explore the problem-solving abilities of preschool principals in Medan, Indonesia, by identifying key challenges they face and analyzing the strategies they employ to address them. The research adopts a qualitative descriptive approach, involving 20 preschool principals in Medan as participants. Data were collected through semi-structured interviews and observations to gain insights into the problem-solving methods applied in various educational scenarios. Thematic analysis was used to identify recurring patterns and strategies in addressing common issues. Practical problem-solving skills among preschool principals are essential for maintaining a well-functioning educational environment. These skills include analytical thinking to identify the root causes of instructional or behavioral issues, decision-making under pressure, conflict resolution between staff or with parents, strategic planning for curriculum and resource development, and collaborative problem-solving that engages teachers in reflective dialogue and peer learning. Training programs focusing on strategic decision-making, leadership development, and conflict resolution can further strengthen their problem-solving abilities, ultimately improving early childhood education in Medan. Studies should also investigate how principal problem-solving styles influence teacher motivation and the sustainability of innovative pedagogical approaches.